2016
DOI: 10.1007/s00423-016-1504-2
|View full text |Cite
|
Sign up to set email alerts
|

Subjective outcome after laparoscopic hiatal hernia repair for intrathoracic stomach

Abstract: PurposeFor decades, an intrathoracic stomach (ITS) has been a definite indication for surgery due to the perceived risk of an acute volvulus with perforation, gangrene, or hemorrhage. At the present time, elective laparoscopic repair is the first choice for treatment of ITS. There is a lack of evidence in the long-term quality of life after a hiatal hernia repair for an intrathoracic stomach.MethodsA retrospective analysis was performed on all patients undergoing a hiatal hernia repair for an intrathoracic sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Since the advent of laparoscopic hiatus hernia surgery in the 1990s [11, 21, 22], multiple studies have demonstrated that this technique effectively treats upper gastrointestinal symptoms secondary to the hiatus hernia and the underlying reflux disease [6, 23, 24]. In the light of these studies, our findings are clinically important, as we have now identified a significant subgroup of patients who do not derive the maximum benefit from their hiatus hernia surgery.…”
Section: Discussionmentioning
confidence: 66%
“…Since the advent of laparoscopic hiatus hernia surgery in the 1990s [11, 21, 22], multiple studies have demonstrated that this technique effectively treats upper gastrointestinal symptoms secondary to the hiatus hernia and the underlying reflux disease [6, 23, 24]. In the light of these studies, our findings are clinically important, as we have now identified a significant subgroup of patients who do not derive the maximum benefit from their hiatus hernia surgery.…”
Section: Discussionmentioning
confidence: 66%
“…The same UK study concluded that the rate of recurrence was significantly lower when oesophageal lengthening by means of Collis gastroplasty was performed [23]. Another recent study on Type III paraoesophageal hernias from the Netherlands, where laparoscopic closure of the hiatus was always combined with an anti-reflux procedure, showed a very low of less than 5% symptomatic recurrence rate, after about 3 years median follow up [24].…”
Section: Editorialmentioning
confidence: 98%
“…He succumbed to a fatal gastropleural fistula 2 months later [49]. Thirdly they could occur intraoperatively from aortic injury especially due to adhesions and anatomical distortion caused by the LHH [61]. They are fortunately a rare occurrence.…”
Section: Mortality Related To Repairmentioning
confidence: 99%
“…Watson [54] declared two perforations, one from a bougie the other was noted on the third postoperative day. Casteljins reported an intraoperative esophageal perforation that required stenting, with subsequent need for resection and conduit formation [61]. Luckily those complications are not very common.…”
Section: Major Intraoperative and Mesh Related Complicationsmentioning
confidence: 99%